Targeting sustainable bioeconomy: A new development strategy for Southern European countries. The Manifesto of the European Mezzogiorno. (20th January 2018) - Koukios, Emmanuel; Monteleone, Massimo; Texeira Carrondo, Manuel Jose; Charalambous, Anthi; Girio, Francisco; Hernández, Eva López; Mannelli, Sofia; Parajó, Juan Carlos; Polycarpou, Polycarpos; Zabaniotou, Anastasia
Abstract: This policy-oriented opinion paper, which has taken the form of a Manifesto, is co-authored by scientists and engineers from Southern European Union countries that are presently experiencing deep and complex systemic crises: Portugal, Spain, Italy, Greece and Cyprus. With their Manifesto, the authors advocate the adoption of a new development model, focusing on the target of sustainable bioeconomy, around which other development themes and topics will crystallize. Implementing this model will act as a locomotive to get the economies and societies of these countries efficiently out of their crises, and smoothly into greener post-crisis pastures. The proposal is articulated in ten critical steps or theses for immediate action by the policy- and decision-makers, as well as industry, markets and other key actors within this troubled area of the European Mezzogiorno. Corroborating evidence of these theses comes in the form of short reports or "letters" on the key topics of this Manifesto from the countries and regions concerned. Graphical abstract: Image Highlights: Targeting sustainable bioeconomy will trigger robust development in Southern Europe. The shift to biobased economy will require strategic changes in many key sectors. Critical will be changes in the policy-, decision-making, and social organisation. Bioeconomy will affect modes and agendas in education, training, and research. The way-forward guidelines take the form of a Manifesto with 10 "commandments".